Penatalaksanaan Pada Pasien Tuberkulosis Paru Melalui Pendekatan Keluarga - Noviana Zara; Rinawati Rinawati (Institut Nalanda, 2023)
Indonesia is ranked second with the most cases of Tuberculosis (TB) in the world. This is due to poor knowledge about TB, smoking habits, and poor adherence to medication. Therefore, it takes the role of a family doctor who can manage patients holistically from various aspects. This study is a case report with primary data sources obtained through anamnesis, physical examination, and supporting examinations. The activities carried out were home visits and completing family guidance sheets, from the data obtained a holistic diagnosis and appropriate management were determined. Patient Mr. A, 68 years old, came for routine TB treatment and was diagnosed two months ago. The patient has normal nutritional status. The problems that the patient has are lack of physical activity, lack of patient knowledge of TB disease, lack of family support, and exposure to cigarette smoke. Pharmacological and non-pharmacological interventions were carried out in patients in the form of education about TB disease in patients and their families. Holistic management of TB patients is needed. The level of patient knowledge of the disease and the importance of the family knowing the treatment schedule and a healthy lifestyle determine the success of TB treatment.